PRICING STRATEGY FOR QUASI-PUBLIC FOREST TOURISM PARK Case Study in Gunung Pancar Forest Tourism Park, Bogor Indonesia - Avenzora, Ricky; Sunarminto, Tutut; Pratiekto, Priyono E.; Lee, Ju Hyoung (Association of Indonesian Forestry and Environment Researchers and Technicians, 2016)
The dynamic of 3-parties conflict of interests (investor, local people and government) in having actual income from the nature tourism park business in Indonesia became worse since a “very progressive” Government Regulation on Forestry Related Services Tariff (so called PP 12/2014) was issued. On one hand, everybody agrees to improve the 17 years old tariff regulation of PP 59/1998. On the other hand, the “unclear reason” of the new tariffs in PP 12/2014 has shocked many parties and created many difficulties while implemented. This paper studies visitors’ expenditures and their willingness to pay (WTP) for every recreation services scenario by using contingent valuation method (CVM) survey with open-ended eliciting questionnaire instrument. Regarding the characteristic of Gunung Pancar Forest Tourism Park (GPFTP) the method was used to justify a reasonable and eligible ticket pricing strategy at the GPFTP as a quasi-public recreation park. The survey has also specifically addressed the reasonable ticket-price that aligns with the financial assumption of investor's business plan and local people's economic activities. Results of the survey show that the continuum of visitors’ WTP is ranging from 3.4 times (as the response to scenario-1) up to 12.7 times (as the response to scenario-5) of the recent ticket price. The WTP of scenario-2, 3 and 4 are ranging from 4.7, 6.2 and 7.5 times, respectively. Furthermore, the results of Tobit Regression Analysis show that seven important variables are positively correlated, while six variables are negatively correlated with the WTP.